VD_FINDINFO Jug / 2022 / 70 vom 7. September 2021 - VD Tribunal cantonal (2021)
CONTRAVENTION, VIOLATION DES RÈGLES DE LA CIRCULATION, MAÎTRISE DU VÉHICULE, DILIGENCE, ACQUITTEMENT | 31 al. 1 LCR, 90 al. 1 LCR, 3 al. 1 OCR